The effect of breastfeeding home visits by integrated health post cadres on mothers’ attitudes toward exclusive breastfeeding : breastfeeding - Suci Deswanti; Hikmah Ifayanti; Rika Agustina; Eka Tri Wulandari (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Exclusive breastfeeding during the first six months of life is an essential effort to improve infant health status and reduce morbidity and mortality rates. However, the coverage of exclusive breastfeeding remains suboptimal, one of which is influenced by mothers’ attitudes toward breastfeeding practices. One of the promotive strategies that can be implemented to develop positive maternal attitudes is breastfeeding home visits conducted by integrated health post cadres). Preliminary data in Pekon Sukamaju indicated that some mothers had not fully practiced exclusive breastfeeding. Purpose: to determine the effect of breastfeeding home visits by integrated health post cadres) on mothers’ attitudes toward exclusive breastfeeding. Method: This study employed a quantitative method with a pre-experimental one group pre-test and post-test design. The population consisted of all mothers with infants aged 0–28 days in Pekon Sukamaju, totaling 25 individuals, with 20 respondents selected using accidental sampling according to inclusion criteria. Data were collected using an attitude questionnaire with a Likert scale administered before and after the home visit intervention. Data analysis was conducted using univariate analysis to determine the mean, standard deviation, minimum, and maximum values, and bivariate analysis using the Paired T-Test with a significance level of α = 0.05. Results: The results showed that the mean score of mothers’ attitudes before the home visit was 33.05 (SD = 6.886), which increased to 48.25 (SD = 6.146) after the intervention. The mean difference of 15.20 indicated an improvement toward a more positive attitude. Conclusion: The Paired T-Test result obtained a p-value of 0.000 (< 0.05), indicating a significant effect of breastfeeding home visits by integrated health post cadres on mothers’ attitudes toward exclusive breastfeeding.